Food Effect Study Design With Oral Drugs: Lessons Learned From Recently Approved Drugs in Oncology. (10th December 2018) - Farha, Mark; Masson, Eric; Tomkinson, Helen; Mugundu, Ganesh
Abstract: Evaluation of the effect of food on the pharmacokinetics of oral oncology drugs is critical to drug development, as food can mitigate or exacerbate toxicities and alter systemic exposure. Our aim is to expand on current US Food and Drug Administration (FDA) guidance and provide data‐driven food‐effect study design recommendations specific to the oncology therapeutic area. Data for recently approved small‐molecule oncology drugs was extracted from the clinical pharmacology review in the sponsor's FDA submission package. Information on subject selection, meal types, timing of the study relative to the pivotal trial, and study outcomes was analyzed. The number of subjects enrolled ranged from 12 to 60, and the majority of studies (19 of 29) were conducted in healthy volunteers. Using AstraZeneca cost data, healthy volunteer studies were estimated to cost 10‐fold less than cancer patient studies. Nine of 29 (31%) studies included meals with multiple levels of fat content. Analysis of a subset of 16 drugs revealed that final results for the food‐effect study were available before the start of the pivotal trial for only 2 drugs. Conducting small food‐effect studies powered to estimate effect, rather than confirm no effect, with only a standardized high‐fat meal according to FDA guidance may eliminate unnecessary studies, reduce cost,  and improve efficiency in oncology drug development. Starting food‐effect studies as early as possible is key to inform dosing in pivotal trials.